The digitalisation of African agriculture report 2018-2019: Executive summary - Tsan, Michael; Totapally, Swetha; Hailu, Michael; Addom, Benjamin K. (CTA / Dalberg Advisors, 2019)
Agricultural transformation is a priority in the policy agenda of African governments in their quest to meet the challenges of food and nutrition insecurity, climate change, youth unemployment and overall economic growth. With the right policies, innovation and investment, the continent’s agriculture could be transformed into a powerhouse not only to feed a growing population but to create decent employment for millions of young people.